Imaging of karst on buried Miocene Carbonate Platform - Fathiyah Jamaludin, S.N. (Institute of Physics Publishing, 2017)
Imaging of carbonate rocks in the subsurface through seismic method is always challenging due to its heterogeneity and fast velocity compared to the other rock types. Existence of karsts features on the carbonate rocks make it more complicated to interpret the reflectors. Utilization of modern interpretation software such as PETREL and GeoTeric® to image the karsts morphology make it possible to model the karst network within the buried carbonate platform used in this study. Using combination of different seismic attributes such as Variance, Conformance, Continuity, Amplitude, Frequency and Edge attributes, we are able to image the karsts features that are available in the proven gas-field in Central Luconia Province, Malaysia. The mentioned attributes are excellent in visualize and image the stratigraphic features based on the difference in their acoustic impedance as well as structural features, which include karst. 2D & 3D Karst Models were developed to give a better understanding on the characteristics of the identified karsts. From the models, it is found that the karsts are concentrated in the top part of the carbonate reservoir (epikarst) and the middle layer with some of them becomes extensive and create karst networks, either laterally or vertically. Most of the vertical network karst are related to the existence of faults that displaced all the horizons in the carbonate platform. © Published under licence by IOP Publishing Ltd.